Measuring optic nerve sheath diameter and lens thickness by b-mode sonographic evaluation in glaucoma - Dagdelen, Kenan (Annals of Medical Research, 2022)
Aim: This study was conducted to measure optic nerve sheath diameter (ONSD) and lens thickness (LT) with B-mode USG in patients with glaucoma and compare them with a healthy control group. Materials and Methods: Seventy-two individuals were recruited, 35 with glaucoma and 37 age- and gender-matched controls without glaucoma. Patients with systemic hypertension, diabetes mellitus, and cataract, history of ocular trauma, higher refractive error, active ophthalmologic infection and smoking were excluded from the study. The ONSD and LT values of both eyes were measured in the supine position using 10MHz frequency B-scan ultrasound. Data analysis was performed by transferring to the SPSS version 25 program. Results: The mean ONSD of glaucomatous eyes (3.60 mm and 3.50 mm on the right and left, respectively) was found to be significantly thinner than the controls (4.20 mm and 4.55 mm on the right and left, respectively). The mean LT of eyes with controls (4.25 mm and 4.15 mm on the right and left, respectively) was significantly lower compared to glaucoma (4.40 mm and 4.30 mm on the right and left, respectively). Conclusion: In glaucoma, sonography is a reliable tool of evaluating the optic nerve sheath diameter and lens thickness.
Keywords: Optic nerve sheath diameter; ONSD; B-Scan ultrasound; lens thickness; glaucoma